Tari Lengger Solasih di Yayasan Satria Suwoko Kabupaten Wonosobo : Kajian Nilai Pendidikan - Mahsa, Edmonda Ruth; Hartono, Hartono (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
The Lengger Solasih Dance at the Satria Suwoko Foundation in Wonosobo Regency is a rich local cultural heritage, encompassing significant educational values such as moral and ethical principles, mutual cooperation, appreciation for culture and history, discipline, creativity, and spirituality. This research is prompted by the challenges of modernization, which have led to a decline in the popularity and public awareness of this dance, thus threatening its preservation. Consequently, this study aims to describe the educational values inherent in the Lengger Solasih Dance and formulate innovative strategies for their effective integration into community learning processes. A qualitative descriptive method was employed for this research , with data collected through observation, in-depth interviews, and documentation at the Satria Wonosobo Foundation, the very place where the Lengger Solasih Dance was developed by the late Mr. Suwoko. The findings indicate that necessary strategies include developing community-based cultural learning programs, fostering collaboration with educational institutions to incorporate the dance into local curricula, utilizing digital media for promotion and education, enhancing the quality of instructors through continuous training, and initiating increased support from the government and relevant stakeholders. Through the implementation of these strategies, it is anticipated that the Lengger Solasih Dance will not only endure as a cultural legacy but also serve as a relevant and inspiring source of learning for shaping the character of Indonesia's younger generation.